Impact of Intrauterine Infusion vs. Subcutaneous G-CSF Injection on Endometrial Immunomodulation and Angiogenesis in Infertile Women Undergoing IUI - Mahmood, Zainab Abdul Qader; Al‑Anbari, Lubna Amer; Al‑Obaidi, Manal Taha (Trends in Immunotherapy, 2025)
Infertility remains a significant global health concern, with endometrial receptivity recognized as a critical factor influencing successful implantation. Granulocyte‑Colony Stimulating Factor (G‑CSF), a hematopoietic cytokine, has recently emerged as a potential therapeutic agent for enhancing endometrial function and modulating immune responses during assisted reproductive procedures. This study aims to investigate the effect of intrauterine infusion versus subcutaneous injection of G‑CSF on immunological and angiogenic markers related to endometrial receptivity in infertile women undergoing intrauterine insemination (IUI). A total of 75 infertile females were enlisted in this prospective interventional comparative trial and were equally divided into three groups: the intrauterine infusion group, the subcutaneous injection group, and the control group (no G‑CSF administration). Baseline demographic and hormonal characteristics, as well as ultrasound and immunological parameters, were recorded before and after G‑CSF administration. Statistical analysis showed no significant differences in demographic and baseline clinical, hormonal, and biochemical characteristics across the groups. Post‑intervention, both G‑CSF groups demonstrated significant improvements in endometrial vascularity indices (pulsatility index, resistance index, and V1/V2 ratio) compared to the control group, despite the endometrial thickness not differing significantly. Serum levels of TNF‑α significantly decreased, while VEGF levels increased significantly post‑G‑CSF in all groups; IL‑10 levels increased but reached significance only in the subcutaneous and control groups. These outcomes indicate that G‑CSF may enhance endometrial receptivity via improved vascular and immunological parameters, although the effect remains inconclusive and requires further validation.